2011
DOI: 10.1590/s0104-07072011000400007
|View full text |Cite
|
Sign up to set email alerts
|

O cotidiano do indivíduo com ferida crônica e sua saúde mental

Abstract: O objetivo deste estudo foi identificar como está a saúde mental das pessoas acometidas por ferida crônica. Pesquisa descritiva de abordagem qualitativa, realizada no período de agosto de 2008 a março de 2009, a qual utilizou a entrevista como técnica para a coleta de dados. Participaram seis portadores de feridas crônicas em acompanhamento pelo Ambulatório de Especialidades de um Hospital Público. Para análise dos dados utilizou-se a técnica de análise de conteúdo. Os resultados demonstram que há perda da aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
31

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 10 publications
0
33
0
31
Order By: Relevance
“…Some studies demonstrated that individuals affected by venous leg ulcers wear clothes that hide the lower limbs because they feel embarrassed and discriminated because of the changes in their body image (15)(16) .…”
Section: Feel So Ashamed Of My Legs Of Myself So I Only Wear Longmentioning
confidence: 99%
“…Some studies demonstrated that individuals affected by venous leg ulcers wear clothes that hide the lower limbs because they feel embarrassed and discriminated because of the changes in their body image (15)(16) .…”
Section: Feel So Ashamed Of My Legs Of Myself So I Only Wear Longmentioning
confidence: 99%
“…Care transcends the treatment of wounds and an integral view of the individual enables the identification of needs and particularities, especially because a wound changes the routines of people and can emotionally and physiologically affect them. 7,23 In this sense, there is a need for professional interventions to go beyond the wound and include assessment and treatment focused on the person as a complex and integral being so that the lack of knowledge regarding care practices and the needs that permeate the search for health services is overcome and incorporates the various health determinants and conditioning factors.…”
Section: We Thought It Was a Little Bruise That You Put Some Ointmentmentioning
confidence: 99%
“…It is essential to consider psychological, social and cultural aspects that are directly connected to the development of this chronic condition. People with chronic wounds must face serious changes in their way of life that can lead to low self-esteem, reduced autonomy and selfcare defi cits (12)(13) . Emotional changes, especially non-acceptance of the lesion and chronic situation, are presented as the main diffi culties faced by nurses when promoting self-esteem, autonomy and self-care.…”
Section: (E1)mentioning
confidence: 99%
“…Some authors (7,10,12,16) emphasize the need to strengthen and establish support networks that include social actors in the lives of people with chronic wounds. These support networks are very important to ensure commitment and inclusion of individuals in the planning of their care, and provide the necessary support for self-esteem, autonomy and self-care.…”
Section: Recovering Support Network: Family and Social Groupsmentioning
confidence: 99%